2022
DOI: 10.3390/ijms23147999
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Formulation and In Vitro Testing in Non-Physiological Conditions Addressed to Ex Vivo Kidney Perfusion

Abstract: This work focuses on formulating liposomes to be used in isolated kidney dynamic machine perfusion in hypothermic conditions as drug delivery systems to improve preservation of transplantable organs. The need mainly arises from use of kidneys from marginal donors for transplantation that are more exposed to ischemic/reperfusion injury compared to those from standard donors. Two liposome preparation techniques, thin film hydration and microfluidic techniques, are explored for formulating liposomes loaded with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The production speed was varied from 4 mL/min to 12 mL/min while aqueous-to-ethanol FRRs among 2 and 6 (namely 2:1–6:1 v : v ) were selected. The levels of each operating factor were set based on past reports [ 18 , 19 , 20 ]. The effect of selected manufacturing parameters on the liposomes’ physical attributes (particle size and polydispersity) was evaluated by a two-level full factorial screening Design of Experiment (DoE).…”
Section: Methodsmentioning
confidence: 99%
“…The production speed was varied from 4 mL/min to 12 mL/min while aqueous-to-ethanol FRRs among 2 and 6 (namely 2:1–6:1 v : v ) were selected. The levels of each operating factor were set based on past reports [ 18 , 19 , 20 ]. The effect of selected manufacturing parameters on the liposomes’ physical attributes (particle size and polydispersity) was evaluated by a two-level full factorial screening Design of Experiment (DoE).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of this assay was carried out using a modified method (Pisani et al, 2022;D'Souza, 2014;Li et al, 2001). The other residue sample obtained from the purification process was transferred into the top part of an ultra-centrifugal filter (Amicon tube, 100,000 MWCO) with a volume (ranging from 600 -700 µL, depending on sample encapsulation efficiency) that is equivalent to 1 mg of BSA.…”
Section: In Vitro Protein Release Assaymentioning
confidence: 99%
“…Both inlet streams were controlled by syringe pumps connected to a computer that controlled the whole process. The total flow rate (TFR) of aqueous and ethanolic streams was 8 mL/min, and the flow rate ratio (FRR) was 3:1, as set in a previous work of the same authors and reported in Table 3-#PM1 [40]. The liposomes preparation process with Nanoassemblr was performed at room temperature (25 ± 3 • C).…”
Section: Empty Liposome Preparation By Microfluidic Techniquementioning
confidence: 99%
“…BSA was loaded into liposomes using the passive method, contextual to liposome preparation (#PM2), as the control. The microfluidic process conditions were those already reported above in Table 3 [40]. BSA was solubilized in MilliQ water (brought to pH 7.4 by NaOH addition) supplemented with trehalose 20% w/w.…”
Section: Empty Liposome Preparation By Microfluidic Techniquementioning
confidence: 99%
See 1 more Smart Citation